“Life Starts for Me Again.” The Social Impact of Psychology on Programs for Homeless People: Solidarity Networks for the Effectiveness of Interventions - Matulič-Domadzič, Virginia; Munté-Pascual, Ariadna; De Vicente-Zueras, Irene; León-Jiménez, Susana (Frontiers in Psychology, 2020)
The role of psychology in the improvement of people’s lives is consistent, according to the scientific literature review. More and more studies within psychology, and other social sciences, are pointing out the importance of the quality of social interactions on physical and mental health and upon perceived wellbeing. When talking about homelessness, psychology has served these individuals mostly by informing intervention programs related to preventing and responding to substance abuse, healthcare, sexual risks, or mental illnesses, and these are key problems that psychology has also studied and found to be connected to homelessness. Such strategies, which were traditionally mostly centered on tackling the weaknesses that homeless people face, are now increasingly considering the role of the social support services. The aim of this study was, on the one hand, to identify evidence on the importance of solidarity as a key factor in the process of overcoming homelessness, and associated substance abuse situations, and the barriers and conditions to achieve it. On another hand, the aim was also to approach the impact of that solidarity on their general wellbeing from the perspective of homeless subjects themselves. To achieve this aim, 20 life stories of people aged 35 to 70 years old were conducted in the metropolitan area of Barcelona. The people interviewed had been homeless in a recent period of their lives and were currently dependent on different services. The communicative methodology allowed deepening into the life stories of these individuals via egalitarian dialogue between the researchers and the participants. The results of the qualitative analysis showed that a strong solidarity network was crucial in the process of overcoming the participants’ homelessness situation and to tackle related circumstances (alcoholism and drug abuse among others), and this has had an impact in their general wellbeing and in the development of more solidarity attitudes. These findings are discussed in light of psychological knowledge and other social sciences literature on the importance of quality social environments to support positive developmental trajectories and considering the potential social impact of the intervention programs that take into account the factor of solidarity during their implementation process.